Private Peers’ Disclosure Transparency and Public Firms’ Information Environment - Beyer, Bianca; Flagmeier, Vanessa; Kosi, Urska
This study examines how private peers’ disclosure transparency affects public firms’ information environment, captured through analyst forecast behavior. Focusing on the most important private firms operating in U.S. industries, we investigate whether private peer disclosure—despite differing substantially from public firm disclosure—is incorporated into analysts’ forecasts. In a cross-sectional analysis, we document lower forecast quality in industries where private peers’ disclosure intensity is low. In contrast, when private peers’ disclosure intensity is high, forecast quality does not differ from that in industries with only public peers. We find consistent results for a subsample of U.S. private peers. Consistent with this interpretation, a difference-in-differences analysis documents increased analyst forecast activity around the disclosure dates of private peers. Together, these findings indicate that analysts incorporate private peers’ information when these peers are both economically important and sufficiently transparent, and highlight that variation in private firms’ disclosure intensity generates heterogenous externalities for public firms. Overall, our evidence supports a cost-benefit trade-off in analysts’ information acquisition, and, by documenting the relevance of private peers’ information for public firms, contributes to the debate on the externalities of private firms’ disclosure transparency.

Poiesis des Selbst. Eine raumtheoretische Bestimmung des ‚Devianz-Orts‘ anhand von Analysen zu Lutz Seilers Romanen «Kruso» und «Stern 111» - Heerdegen, Björn

The spatial and sectoral incidence of Germany’s COVID-19 insolvency gap - Rahali, Mahdi; Kosi, Urska; Gassen, Joachim

Dissemination of information by small caps - Böing, Dennis; Kosi, Urska

Exploring serum biomarkers in paediatric psychiatry: the impact of NfL and GFAP - Pawlitzki, Marc; Masanneck, Lars; Schlarbaum, Laura; Jankovic, Nicole; Bittner, Stefan; Steffen, Falk; Kuhle, Jens; Benkert, Pascal; Repple, Jonathan; Bühlmeier, Judith; Hinney, Anke; Hebebrand, Johannes; et al. (Translational Psychiatry)
Abstract Serum neurofilament light chain (sNfL) and glial fibrillary acidic protein (GFAP) are biomarkers of neuroaxonal and astrocytic damage but remain understudied in adolescent psychiatric populations. This study investigated sNfL and GFAP levels in 412 adolescents diagnosed with anorexia nervosa (AN) ( n = 52), depression ( n = 237), and other psychiatric disorders ( n = 123). We assessed their diagnostic utility, correlation with disease severity, and longitudinal changes during AN treatment. Biomarkers were measured using Single Molecule Array technology, with Z-scores derived from reference datasets. Compared to population norms, both biomarkers were elevated in AN (sNfL: 1.15 ± 1.17; GFAP: 1.50 ± 0.84) and in depression (sNfL: 0.34 ± 1.10; GFAP: 0.58 ± 1.00). Patients with AN showed significantly higher biomarker levels than those with depression or other psychiatric disorders; importantly, this distinction remained evident in sensitivity analyses restricted to underweight individuals with depression. In AN, sNfL levels correlated with baseline weight loss (β = −0.45, R² = 0.20) and declined significantly during treatment, while GFAP changes were less pronounced. Neither marker correlated with depressive symptom severity. Bootstrapped ROC analyses showed moderate-to-good discriminatory power (AUCs 0.70–0.84) for distinguishing AN from depression. These findings suggest that neuroaxonal and astrocytic stress is a component of adolescent psychopathology, particularly in AN. sNfL appears sensitive to starvation-related neurobiological changes, with levels normalizing alongside weight restoration. GFAP showed similar but less robust trends. Accordingly, the observed biomarker changes reflect more than underweight alone, supporting a potential role in differential diagnosis and treatment monitoring.

Vitamin D, inflammation and depressive symptoms in adolescents: analysis using observational and interventional data - Schlarbaum, Laura; Jankovic, N.; Engler, H.; Hirtz, R.; Grasemann, C.; Peters, T.; Hinney, A.; Antel, J.; Hebebrand, J.; Föcker, M.; Libuda, Lars (Neuroscience Applied)

Kulturelles Lernen im Fremdsprachenunterricht unterstützen - Frankemölle, Bernd (Die Wirksamkeit von Lehr-/Lernmethoden im Fremdsprachenunterricht. Empirische Befunde für Lehrkräfte und Unterricht)

The role of digital teaching experience for learning about digital as well as inter- and transcultural foreign language teaching in a web-based training - Frankemölle, Bernd; Göbel, Kerstin (Digital and AI Competence in Subject-Specific Education)

Double Hall algebras and derived equivalences revisited - Burban, Igor; Perniok, Daniel
Let $\mathbb{k}$ be a finite field and $\mathcal{A}, \mathcal{B}$ be $\mathbb{k}$-linear $\mathsf{Ext}$-finite hereditary abelian categories. A theorem of Cramer asserts that, under suitable assumptions, a derived equivalence $\mathcal{D}^b(\mathcal{A}) \!\longrightarrow\! \mathcal{D}^b(\mathcal{B})$ between two such categories induces an algebra isomorphism of the corresponding double Hall algebras $\mathsf{DH}_\mathcal{A} \!\longrightarrow\! \mathsf{DH}_\mathcal{B}$. It turns out that a counting formula for certain distinguished triangles in $\mathcal{D}^b(\mathcal{A})$, on which Cramer's proof relies, is incorrect in general. We give a corrected proof of Cramer's theorem which preserves the overall strategy of his approach.

Handlungsorientierung in der Ausbildung von Lehrkräften und pädagogischen Fachkräften. Konzeptionen und Forschungsperspektiven
Eine zentrale Herausforderung in der Professionalisierung pädagogischer Fach- und Lehrkräfte besteht in der Relation von eher theoretischen und praktischen Ausbildungsbestandteilen. Beispielsweise fühlen sich angehende Lehrkräfte durch ihr Studium häufig nicht ausreichend auf die beruflichen Anforderungen vorbereitet. Daher wird verstärkt versucht, Curricula von Ausbildungs- und Studiengängen deutlicher an den tatsächlichen professionellen Handlungsanforderungen zu orientieren und auch in frühen Ausbildungsphasen verstärkt Elemente beruflicher Praxis zu integrieren. Dieser Band nimmt die Handlungsorientierung in der Ausbildung von Lehrkräften und pädagogischen Fachkräften theoretisch-konzeptionell sowie empirisch in den Blick. Zudem werden innovative Lehransätze aufgezeigt, die den Fokus auf eine Stärkung einer solchen Handlungsorientierung legen, z.B. durch simulationsbasierte Lern- und Prüfungsformate. Es handelt sich um den zweiten Band der Reihe Paderborner Beiträge zur Bildungsforschung und Lehrkräftebildung, die von der PLAZ – Professional School of Education herausgegeben wird.

(Neo-)Kantian Foundation of Foundations: The Göttingen Case - Peckhaus, Volker (New Perspectives on Neo-Kantianism and the Sciences)

1. Heiner-Müller-Jahrbuch 1: Heiner Müllers Natur.

Wave Front Sets of Nilpotent Lie Group Representations - Weich, Tobias; Budde, Julia (Journal of Functional Analysis)

Travelling Stonemasons and the Architectural Cultural Exchange between Spain, Mexico, and Peru in the 16th Century: Connections and Paths of the Toribio de Alcaraz Family - Silvestri, Marco (Art, Travel, and Exchange between Iberia and Global Geographies, c. 1400–1550)

Facetten der Germanistischen Linguistik: Bestandsaufnahme und Perspektiven - Schuster, Britt-Marie; Bubenhofer, Noah (Germanistische Linguistik. Genese, Zustand und Zukunft eines Faches im Spiegel der RGL)

Germanistische Linguistik. Genese, Zustand und Zukunft eines Faches im Spiegel der RGL

Water in the Micropores of CPO-27 Metal-Organic Frameworks: A Comprehensive Study - Kloß, Marvin; Weinberger, Christian; Tiemann, Michael (Microporous and Mesoporous Materials)
The metal-organic framework CPO-27 exhibits free coordination sites (open metal sites) and can be prepared with a wide range of metals that influence its properties. It is therefore an intriguing structure to study sorption phenomena. We analyze the water resistance and sorption behavior of these frameworks, with particular attention to the sorption mechanism in detail and the structure of the confined water molecules. For this purpose, we use manometric water vapor sorption analysis and FTIR spectroscopy. The respective metal center orchestrates both the adsorption behavior and the arrangement of the water molecules in the micropores of the framework. The extent to which water molecules form hydrogen bonds (with each other and with framework oxygen atoms) plays a crucial role in the stability of the framework towards water. Water adsorption is governed by the coordination of water molecules to the open metal sites (except for CPO-27-Cu) and subsequent H-bonding. A stepwise adsorption of water is observed, with significant differences depending on the choice of metal.

Absence of dead-core formations in chemotaxis systems with degenerate diffusion - Black, Tobias (Applied Mathematics Letters)

Symposium—Towards innovative practices in mathematics education: Teachers’ and students’ choice and use of digital resources - Pepin, Birgit; Rezat, Sebastian (Recent Advances in Mathematics Textbook Research and Development)
Abstract In this symposium we investigate students’ agency of selecting and using (digital) resources for developing their own learning paths. For that, we first review the literature related to students’ selection and use of resources in mathematics education in different pedagogical settings (presentation 1). Second, we develop insights from the different studies that participate in this symposium (presentation 2–6), at school as well as at university level. Results show that attempts have been made to provide students opportunities to develop agency of their mathematics learning, in particular with the development and provision of numerous digital tools and learning resources at university level and related to innovative pedagogical approaches. At the same time, it is not obvious how these tools and resources help students to develop deeper conceptual understandings. Certainly, students often ‘demand’ more student-centered and autonomous education approaches (e.g., at university level), also in mathematics education. Further, it seems that authentic problem-based education approaches are more motivating for students. These ‘innovative’ approaches necessitate particular types of structure and support for students. Moreover, they require different ways of providing resources that students can and want to interact with, and that help students to navigate through the curriculum to develop their own learning paths. At the same time, teachers also need support on how to orchestrate student learning with the available resources in such environments, so to be able to attend to students’ individual needs. The symposium comprised altogether six presentations: Birgit Pepin & Sebastian Rezat: Students’ agency of selecting and using (digital) resources for developing their own learning paths: An overview Annalisa Cusi & Agnese I. Telloni: Learning through digital curriculum resource design: students’ reflections on their role as designers Vilma Mesa, Lelia Burley-Sanford, Xinyi Hao, & Carlos Quiroz: Interactive features in university textbooks and their use by teachers and students Sebastian Rezat: Fostering university students’ reading and understanding of mathematical text in a flipped classroom approach with a digital marking tool Birgit Pepin & Ulises Salinas: Challenge/problem-based mathematics learning at university level: The case of the modeling week Farzad Radmehr: Problem-posing: An inclusive activity for improving teaching and learning of mathematics at university level

Fostering university students’ reading and understanding of mathematical text in a flipped classroom approach with a digital marking tool - Rezat, Sebastian (Recent Advances in Mathematics Textbook Research and Development)
Abstract Even in the digital age, learning mathematics at an academic level still requires much interaction with mathematical texts. Understanding and developing disciplinary literacy skills at all levels is an increasing matter of interest.